ANALISIS KESALAHAN DALAM MENYELESAIKAN OPERASI HITUNG CAMPURAN BILANGAN BULAT SISWA KELAS V SEKOLAH DASAR - Nanda Dwi Putri; Syahrilfuddin; Guslinda (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This article examines the types of errors made by fifth-grade elementary school students in solving mixed integer arithmetic operations. Previous research indicated a high frequency of errors in this learning material, prompting the need for an in-depth analysis. This study employs a qualitative research design, using question-form tests, interviews, and documentation as instruments. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results reveal that students’ errors consisted of 54% conceptual errors, 28% arithmetic errors, and 18% mixed errors. These findings highlight the need for teachers and prospective teachers to address and prevent recurring mistakes in teaching mixed integer arithmetic operations.